1980
DOI: 10.1007/bf00584269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of potential blood substitutes (Perfluorochemicals) on rat liver and spleen

Abstract: The effect of an emulsion of perfluorochemicals (PFC) (7 parts perfluorodecalin and 3 parts perfluorotripropylamine, 4.4 g PFC/kg body weight) on organ function was determined. Whereas maximal storage of PFC was reached in the spleen as early as 12 h after PFC administration, the liver attained a maximal PFC content only after 2 days. The increase in weight also differed: a maximum occurred in the spleen on the 4th day, in the liver on the 8th day. Indocyanine green (ICG) clearance showed a small decrease, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…The differences between these results and ours probably are due to the nature of the test particles used: colloidal carbon vs incompatible red cells. Also, though less likely, the differences could have been due to the lower PFC dose (4.4 g/kg) used in the carbon clearance studies [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between these results and ours probably are due to the nature of the test particles used: colloidal carbon vs incompatible red cells. Also, though less likely, the differences could have been due to the lower PFC dose (4.4 g/kg) used in the carbon clearance studies [3].…”
Section: Discussionmentioning
confidence: 99%
“…After intravenous injection, perfluorochemical particles are cleared from the blood and stored within the phagocytic cells of the reticuloendothelial system (RES) [2]. Transient depression of RES phagocytic function has been shown in perfluorocarbon-injected rats [3] with the colloidal carbon clearance method. Preliminary studies in nonhuman primates also suggest that perfluorocarbons inhibit RES function [4].…”
Section: Introductionmentioning
confidence: 99%
“…In previous experiments [15], it was demonstrated that Fluosol-DA (FDA) can dissolve 6.12 ml O2/dl under a pure oxygen atmosphere; at an arterial oxygen pressure of 450 mm Hg [60 kPa] -as received by an inspiratory 02 fraction of -> 0.9 -this corresponds to an oxygen content of 3.62 ml O2/dl. After injection and dilution with the remaining blood volume an additional Oe content of about 1 ml/dl will result.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen content of the blood was increased by perfluorochemicals (PFC). Because PFC reduces the activity of the reticulo-endothelial system [13], RES function was increased by a pretreatment with E. coli endotoxin what gave a full compensation of RES activity [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation